Représentations et usages du territoire, exemple de dialogue entre héritage culturel marron et politique patrimoniale européenne : le cas des abattis Kotika, commune de Papaïchton (Guyane française) - Egle Barone Visigalli; Kristen Sarge (Études Caribéennes)
This article questions the registration process in the inventory of natural sites and monuments protected under the environment. What protections truly offer this tool, especially in the French territories “overseas”? How to reconcile environmental protection, heritage creation and economic development? The listing criteria, defined in 1930 and which have a vision "universal" – a western view – of the environment, have they ever been discussed and submitted for approval and to the sensitivity of the populations concerned, in this case the Bushinenge people? And what do we mean exactly by "heritage site"?